Her perfect life eaudiobook - Ryan, Hank Phillippi (Macmillan Audio, 2021)
"Angela Dawe narrates a complicated mystery of missing siblings, strange news sources, and the seemingly perfect life of a news anchor that could be destroyed due to a decades-old mystery." - AudioFile Magazine The next thrilling standalone novel by USA Today bestselling author Hank Phillippi Ryan . Everyone knows Lily Atwood—and that may be her biggest problem. The beloved television reporter has it all—fame, fortune, Emmys, an adorable seven-year-old daughter, and the hashtag her loving fans created: #PerfectLily. To keep it, all she has to do is protect one life-changing secret. Her own. Lily has an anonymous source who feeds her story tips—but suddenly, the source begins telling Lily inside information about her own life. How does he—or she—know the truth? Lily understands that no one reveals a secret unless they have a reason. Now she's terrified someone is determined to destroy her world—and with it, everyone and everything she holds dear. How much will she risk to keep her perfect life? A Macmillan Audio production from Forge Books